E-Governance Philippine Information Agency (PIA) services through ICTS - Bernardo, Emmanuel R.; Ramos, Alana G. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2013)
A government that is unified and accessible to the people is the primary goal of any government. Various types of government have tried this and failed miserably. But with the advancement of technology, a new avenue of governing was opened that made a unified government possible. With the emergence of Information and Communications Technology, new possibilities were opened that would help create better governance. With that, this study takes the opportunity to study how the Philippine government communicates with its people. This study primarily focuses on the concerns of sufficiency, efficiency, and effectiveness of the E-Governance program of the Philippine Information Agency. This research will be analyzed from the perspective of Information Specialists, its clients, and the staff of PIA in order to have a focused and reliable description, analysis and assessment of the policy.
In this study, it has been revealed that, the PIA owns a great infrastructure and network that is able to fulfill most of its functions and services but what the PIA lacks is sufficient planning for its communications projects; and together with insufficient number of skilled personnel to effectively implement its services, the PIA is unable to fully deliver results. The PIA majorly lacks production-capabilities for its projects and a research-based communication planning and also an impact/effect evaluation after every project is very concerning.
The PIA is open in using new media and social media to deliver its services, but monitoring the digital space is difficult and there is no systematized way of monitoring is implemented yet. New media has a lot of potential but the PIA is not yet able to fully utilize it because of the lack of ICT skilled personnel and the lack of sufficient monitoring that could cover the ever evolving digital media. Various changes must be implemented and development of the staff is a priority for it to function optimally and serve the people's and the country's needs."
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Philippine Information Agency; Internet in public administration -- Philippines -- Quezon City; Information and communications technology (ICT).